2019
DOI: 10.1136/bmjspcare-2019-001894
|View full text |Cite
|
Sign up to set email alerts
|

Adult Child-Parent Dyadic Interactions at the End of Life: A Scoping Review

Abstract: BackgroundBeing terminally ill affects not only the life of patients but also that of their loved ones. Dyads of adult children and their parents at the end of life may face specific challenges with regard to their relationship and interactions that need to be further examined.AimThe aim was to identify, describe and summarise available evidence on adult child–parent interaction and psychosocial support needs at the end of life. Research gaps in the existing literature are disclosed and recommendations for fut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…In the proposed project, a greater number of interviews will be needed, because the project will apply purposeful sampling to include participants with heterogeneous characteristics, with regards to gender, age, immigrant background, employment status and urban/rural residency. Moreover, the study will consider a similar range of characteristics amongst care recipients, on the assumption that such features may reflect meaningful differences in experiences and needs [ 55 , 56 ]. For instance, the project will include patients of varying ages and kinship relations to the LD caregiver, in order to examine any effects of these variables [ 55 , 56 ].…”
Section: Methods and Designmentioning
confidence: 99%
See 1 more Smart Citation
“…In the proposed project, a greater number of interviews will be needed, because the project will apply purposeful sampling to include participants with heterogeneous characteristics, with regards to gender, age, immigrant background, employment status and urban/rural residency. Moreover, the study will consider a similar range of characteristics amongst care recipients, on the assumption that such features may reflect meaningful differences in experiences and needs [ 55 , 56 ]. For instance, the project will include patients of varying ages and kinship relations to the LD caregiver, in order to examine any effects of these variables [ 55 , 56 ].…”
Section: Methods and Designmentioning
confidence: 99%
“…Moreover, the study will consider a similar range of characteristics amongst care recipients, on the assumption that such features may reflect meaningful differences in experiences and needs [ 55 , 56 ]. For instance, the project will include patients of varying ages and kinship relations to the LD caregiver, in order to examine any effects of these variables [ 55 , 56 ]. In total, the project will enroll approximately 30–35 LD caregivers.…”
Section: Methods and Designmentioning
confidence: 99%
“…A topical scoping review 10 showed that no study has examined adult child-parent relationships in the context of two specific dyads: (1) terminally ill adult children and their parents and (2) terminally ill parents and their adult children. The limited body of literature on adult child-parent caregiving relationships at the end of life indicates that, in both dyads, reciprocity and mutual support are perceived as constituent elements of the caregiving relationship.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the desired levels of support in managing endof-life situations, both adult child caregivers and the parents of ill adult children seek information on the patient's illness and perceive such information as helpful, because it enables them to take some control over the situation [10][11][12][13]. The term "caregiver" is used in this article in a broad sense, encompassing family members who provide practical and/ or emotional support.…”
Section: Introductionmentioning
confidence: 99%